Timber and herring : modernisation and mobility in Finnish Lapland and the Western Islands of Scotland, 1770-1970 - Kumpulainen, Riitta (2009)
Only abstract. Paper copies of master’s theses are listed in the Helka database (http://www.helsinki.fi/helka). Electronic copies of master’s theses are either available as open access or only on thesis terminals in the Helsinki University Library. Vain tiivistelmä. Sidottujen gradujen saatavuuden voit tarkistaa Helka-tietokannasta (http://www.helsinki.fi/helka). Digitaaliset gradut voivat olla luettavissa avoimesti verkossa tai rajoitetusti kirjaston opinnäytekioskeilla. Endast sammandrag. Inbundna avhandlingar kan sökas i Helka-databasen (http://www.helsinki.fi/helka). Elektroniska kopior av avhandlingar finns antingen öppet på nätet eller endast tillgängliga i bibliotekets avhandlingsterminaler. The present study is historical and comparative by nature. The research problem consists of two domains. The first one deals with the consequences of the proceeding modernisation process in the two peripheral areas of Finnish Lapland and the Western Islands of Scotland. Indicators such as economic development, population development, changes in political and religious atmosphere and spread of public education have been discussed to show that although the modernisation process has proceeded differently in each area, both have remained economically backward and culturally distinct when compared to the rest of the country. This has been interpreted to reflect an institutionalised cultural division of labour, as Michael Hechter's (1975) concept of internal colonialism suggests. Because increasing labour mobility and particularly seasonal mobility is one of the most pronounced consequences of the modernisation process in both areas, it has been studied as the second domain. By studying seasonal mobility, an attempt to grasp the individual experience of a structural change has been made. In Scotland, the East Coast herring industry offered seasonal work for the Islanders between 1850-1939 and in Finland, the developing forest industry for the lumberjacks and road builders from the beginning of the century until the ...